Review of deep fluids in sedimentary basins and their influence on resources, with a focus on oil and geothermal exploitation - Lu, Jia; Li, Chuanming; Wang, Maoyun; Zhang, Chengju (Frontiers in Earth Science, 2023)
Deep fluid activity is very common in large oil-gas basins worldwide. Deep fluids as the links between internal and external factors of a basin run in the way of organic-inorganic interactions through the oil-gas formation and aggregation. Herein, the identifying characteristics of deep fluids in sedimentary basins as well as their oil-gas reservoir formation and geothermal resource effects are summarized. The deep fluids of sedimentary basins are identified from three aspects, including mineral composition, fluid inclusions, and geochemical characteristics. The effects of deepfluid activity on oil-gas reservoir formation are manifested in two major aspects of matter and energy. As for the matter effects, deep fluids can improve the primary productivity of sedimentary basins, and carry abundant inorganic hydrogen, which contributes to improving the hydrocarbon productivity through hydrogenation. As for the energy effects, the heat energy of deep fluids can promote the mature evolution from organic matter to oil-gas. During this process, the heating of deep fluids will cause the thinning of oil-generating window depth of hydrocarbon source rocks, and can generate very high pressure, promoting the discharge of abundant hydrocarbons formed by hydrocarbon source rocks. Furthermore, deep fluids can directly form volcanic rock oil gas reservoirs. And another manifestation of deep fluid energy is geothermal. And the thermal energy of deep fluids can directly form hot dry rocks, which is the most important existing form of geothermal resources. The geological exploration of hot dry rocks should be supported by further geochemical and geophysical research.